A rare case of dysphonia in mitochondrial myopathy - Kumari, Abha; Goyal, Sunil; Malik, Virender; Singh, Takhellambam Biram; Paramasivan, Vijay Krishnan; Kameswaran, Mohan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
The mitochondrial myopathy consists of diverse group of disorders which is characterized by primary dysfunction of mitochondrial respiratory chain leading to muscle disease. The involvement of larynx is very rare and only few cases have been reported in the literature. This study presents the fourth published case of dysphonia in the setting of mitochondrial myopathy. A patient with dysphonia with laryngeal involvement in mitochondrial myopathy is presented with literature review. A 43 year old man presented with progressive dysphonia and muscle weakness. Laryngeal examination showed bilateral adductor weakness of vocal cords and biopsy revealed findings typical of mitochondrial myopathy (MM). He underwent conservative trial for dysphonia with no relief and subsequently medalization thyroplasty showed some improvement in dysphonia. Mitochondrial myopathy should be considered in the differential diagnosis of dysphonia for early diagnosis and management.